Tests for Platelet Changes, Acute Phase Reactants and Serum Lipids in Diabetes mellitus and Peripheral Vascular Disease - van Oost, B A; Veldhuyzen, B F E; van Houwelingen, H C; Timmermans, A P M; Sixma, J J (Thrombosis and Haemostasis, 1982)
Platelets tests, acute phase reactants and serum lipids were measured in patients with diabetes mellitus and patients with peripheral vascular disease. Patients frequently had abnormal platelet tests and significantly increased acute phase reactants and serum lipids, compared to young healthy control subjects. These differences were compared with multidiscriminant analysis. Patients could be separated in part from the control subjects with variables derived from the measurement of acute phase proteins and serum lipids. Platelet test results improved the separation between diabetics and control subjects, but not between patients with peripheral vascular disease and control subjects. Diabetic patients with severe retinopathy frequently had evidence of platelet activation. They also had increased acute phase reactants and serum lipids compared to diabetics with absent or nonproliferative retinopathy. In patients with peripheral vascular disease, only the fibrinogen concentration was related to the degree of vessel damage by arteriography.
Keywords: Diabetes mellitus; Peripheral vascular disease; Platelet density; β-thromboglobulin